Patrões, fregueses e donos : economia e xamanismo no médio rio Negro - Nascimento, Luiz Augusto Sousa do (2017)
The thesis is the result of an ethnographic research in the Middle Rio Negro region of the Amazonian northwest. This region is inhabited by multiethnic populations (Arawak, Eastern Tukano and Yanomami), predominantly for the baré group, which participates in a broad process of sociality with multiple agents, both human and nonhuman. It is tried to present the perspective of the Baré as to the economic system of which they participate, considering this wide range of relations. From the narratives and reports from daily life, I address issues such as the occupation of the present territory, the constitution of communities, work on the extraction of piaçaba and its link with other worlds and their owners. From the baré point of view, I try to elaborate an anthropological reflection about the main gears of the economic system in which they participate - the regime de aviamento, in which patrons and customers connect in symmetrical and asymmetric relations. In this context, I discuss the encounters between humans and non-humans in different social spaces: the river, the forest and the community. The meetings in these spaces are a complex and complex system that includes patrons, patrons, owners, recipients, prayers, shamans, enchants, and whose synthesis can be taken from a baré story: "Together and mixed are true peoples, inhabitants of the forest and Rivers ".